1997
DOI: 10.1017/s1357729800008675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food level on performance and behaviour of sows in a dynamic group-housing system with electronic feeding

Abstract: Evidence from studies of group-housed sows in unbedded systems indicates that hunger may be a cause of increased aggression between animals. The present study aimed to investigate the effects of food level on performance, aggression and skin damage in a deep-straw system. Sixteen groups offive gilts were introduced over 8 months to one of two dynamic groups in a deep-straw yard (2·35 m2 per sow) receiving different food levels from an electronic sow-feeding system: high (H: 3·0 kg and 38 MJ/day) and low (L: 1·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Results of the current study demonstrated that aggression among sows decreased 6 h after mixing, similar to that observed in other studies (Moor et al, 1993;Spoolder et al, 1997;Arey, 1999). No further decrease in aggression was observed among sows between 6 and 72 h after mixing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the current study demonstrated that aggression among sows decreased 6 h after mixing, similar to that observed in other studies (Moor et al, 1993;Spoolder et al, 1997;Arey, 1999). No further decrease in aggression was observed among sows between 6 and 72 h after mixing.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the effect of supplementing synthetic Trp on controlling aggression among limit-fed gestating sows in' the current study might be short-lived after feeding. Furthermore, limit-feeding increases the motivation for fighting in gestating sows (Spoolder et al, 1997), as well as in breeders of other species (Shea et al, 1990). The combination of a minimal nutrient supply and high motivation for fighting may increase the threshold of dietary "'"Means without a common superscript within a row differ {P < 0.05).°' 'Means without a common superscript within a row tend to differ {P < 0.10).…”
Section: Discussionmentioning
confidence: 99%
“…Fights aimed at determining dominance relationships generally do not last more than 1 -2 days following the mixing of unfamiliar animals (e.g. Spoolder et al, 1997;Arey and Edwards, 1998), but fights over access to feed can be a daily recurrent event, depending on the feeding method. In both situations the animals tend to develop a so called 'avoidance order' (Jensen, 1982;Jensen and Wood-Gush, 1984), which helps to minimise aggression and is closely linked to the dominance hierarchy formed.…”
Section: Access To Foraging/exploration Materialsmentioning
confidence: 99%
“…There are several studies which have quantified the level of injuries following social interactions (e.g. Weng et al, 1998;Spoolder et al, 1997;Docking et al, 2000). These are generally based on a count or an estimation of the number of lesions, usually categorised according to seriousness.…”
Section: Access To Foraging/exploration Materialsmentioning
confidence: 99%
See 1 more Smart Citation